Cycling of waste fusel alcohols from sugar cane industries using supercritical carbon dioxide - Pereira, F. S. [UNESP]; Pereira, L. J. [UNESP]; Credito, D. F. A. [UNESP]; Girao, L. H. V. [UNESP]; Idehara, A. H. S. [UNESP]; Gonzalez, E. R. P. [UNESP] (Royal Soc Chemistry, 2015)
The present study describes the clean synthesis of non-phosgene organic carbonates (NPOCs) from a selective multicomponent reaction with two important by-products from sugar and alcohol industries, namely, fusel alcohols and carbon dioxide, in the presence of 1,8-diazabicycloundecene (DBU), 1,5-diazabicyclo[4.3.0]-non-5-ene (DBN) or 1,3,4,6,7,8-hexahydro-2H-pyrimido[1,2-a]-pyrimidine (TBD) and an alkylating agent. The bases were used for the nucleophilic activation of the alcohols. The synthesis of carbonates was carried out without solvent and confirmed by GC-MS with EI ionization mode, H-1- and C-13-NMR and FT-IR analysis. The carbonates were obtained in excellent yields. Crude fusel alcohol can be converted to alkylcarbonates. The proposed methodology can also be employed to convert other hydroxylated compounds into carbonates.